Molecular diagnostics identifies risks for graft dysfunction despite borderline histologic changes - Hrubá, Petra; Brabcová, Irena; Gueler, Faikah; Krejčík, Zdeněk; Stránecký, Viktor; Svobodová, Eva; Malušková, Jana; Gwinner, Wilfried; Honsová, Eva; Lodererová, Alena; Oberbauer, Rainer; Zachoval, Roman; et al. (Kidney international, 2015)
The significance of borderline changes in kidney allograft biopsies is widely debated. To help resolve this, we studied differences in intrarenal gene expression patterns between early clinical and 3-month protocol biopsies, all of which had borderline histologic changes. The gene expression profiles in training set of patients by microarray analysis and data were validated in a larger cohort using RT-qPCR. There was greater expression of immunity- and inflammation-related genes in the early clinical biopsies compared to the 3-month protocol biopsies with borderline changes. In early clinically manifested borderline changes, graft deterioration within 24 months due to chronic rejection was associated with increased activation of immune, defense, and inflammatory processes. Regression modeling identified higher donor age and expression of macrophage receptor CLEC5A as risk factors for progression. In the 3-month protocol biopsies with borderline changes, graft dysfunction was associated with increased expression of fibrinogen complex transcripts. The discrimination power of fibrinogen was confirmed by cross-validation on two independent cohorts. Thus, our study highlights variations in gene expression between clinical and subclinical borderline changes despite similar histological findings. The data also support a recommendation for frequent patient monitoring, especially in those with borderline changes who received grafts from older donors.
Keywords: Graft Rejection; Male; Oligonucleotide Array Sequence Analysis; Treatment Outcome; Polymerase Chain Reaction; polymerázová řetězová reakce; lidé středního věku; Time Factors; retrospektivní studie; genetické markery; rejekce štěpu; Kidney Transplantation; prediktivní hodnota testů; časové faktory; transplantace ledvin; stanovení celkové genové exprese; Humans; Phenotype; Reproducibility of Results; Middle Aged; Molecular Diagnostic Techniques; senioři; rizikové faktory; reprodukovatelnost výsledků; hodnocení rizik; mužské pohlaví; Gene Expression Regulation; Female; Early Diagnosis; Asymptomatic Diseases; Predictive Value of Tests; Kidney; Aged; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; ženské pohlaví; regulace genové exprese; asymptomatické nemoci; Retrospective Studies; Genetic Predisposition to Disease; Adult; ledviny; diagnostické techniky molekulární; Gene Expression Profiling; Biopsy; časná diagnóza; genetická predispozice k nemoci; dospělí; lidé; Risk Factors; fenotyp; Risk Assessment; Genetic Markers; biopsie; výsledek terapie